Motiv mesta v slovenski mladinski književnosti - Blažič, Milena (Urbani izziv, 2003)
The article presents the city as motif of Slovenian youth literature in four different periods, beginning in the first period of original Slovenian youth literature in the second half of the 19. century, second period in the first half of the 20. century, third period in the second half of the 20. century and after 1950, when significant books were produced in the field of short modern stories, emphasising on picture books and realistic narrative prose, and the fourth period after 1990. A discernable shift can be observed in the thirties of the 20. century, during the times of socialist realism. The most significant change occurred after 1960, when massive migration from rural to urban environments caused by industrialisation began. The motif of urban environment especially marked modern realistic narrative, coined problematic narrative after 1990, with its focus on issues of growing up in such environments. The city as motif or theme doesn't appear only in realistic narrative, but since the early 20. century also in fantastic narrative, thus it dichotomically presents the image of real world in Slovenian youth realistic narrative.
Keywords: literarni motivi; mesta; podoba; slovenska mladinska književnost